2012
DOI: 10.1021/es2039008
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Toxicity of Nano-C60 Aggregates: More Sensitive Indication by Apoptosis-Related Bax Translocation in Cultured Human Cells

Abstract: The toxicity of NPs is not well characterized in terms of their size. In particular, the size-based toxicity of fullerene (C(60)) remains an issue because of a lack of C(60) NPs with a well-controlled size. In this work, six fractions of the nano-C(60) aggregates (nC(60)) with different size distribution were prepared by a simple differential centrifugation. By using these nC(60) fractions, we demonstrate the size-dependent inhibition of DNA polymerase and reduced-size enhanced cytotoxicity. Above all, we foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 42 publications
1
27
0
2
Order By: Relevance
“…Our data indicate that the pH value, which has rarely been mentioned previously, is closely related to nC 60 biological activity. Low pH and high nC 60 concentrations promote the formation of nC 60 aggregates with larger diameters (Rudalevige et al, 1998;Fortner et al, 2005) and might subsequently attenuate nC 60 toxicity (Song et al, 2012). The biological effect of colloidal fullerene is to a large extent determined by environment factors.…”
Section: Discussionmentioning
confidence: 99%
“…Our data indicate that the pH value, which has rarely been mentioned previously, is closely related to nC 60 biological activity. Low pH and high nC 60 concentrations promote the formation of nC 60 aggregates with larger diameters (Rudalevige et al, 1998;Fortner et al, 2005) and might subsequently attenuate nC 60 toxicity (Song et al, 2012). The biological effect of colloidal fullerene is to a large extent determined by environment factors.…”
Section: Discussionmentioning
confidence: 99%
“…Though studies have shown that nanomaterials might have deleterious side effects (Nel et al, 2006;Song et al, 2012;Song et al, 2013), few reports on GO toxicity have been published so far. Akhavan and Ghaderi (2010) integrity upon exposure to GO (Tazawa et al, 2007) based on analysis by transmission electron microscopy (TEM).…”
Section: Introductionmentioning
confidence: 99%
“…The huge application potentials of these promising nanomaterials have strongly stimulated their production and consumption [2]. Inevitably, carbon nanoparticles (CNPs) have come into the environment [3,4] and have a strong possibility of posing health risks to human [5] and ecological species [6] because of their specific properties. The environmental health and safety risks of CNPs in society have thus become a serious concern in academia.…”
Section: Introductionmentioning
confidence: 99%